Corporate foresight at the strategic research institutes - Sacio-Szymańska, Anna; Mazurkiewicz, Adam; Poteralska, Beata (Business: Theory and Practice, 2015)
Foresight – that is systematic, in-depth analyses of social, technological, economic, environmental and political development trends in order to anticipate their impact on organisation, sector or a region in a long term perspective supports taking effective strategic and operational decisions at different organisational levels and thus shapes a country’s economic development. The paper gives an overview of the corporate foresight process realised at the Institute for Sustainable Technologies – National Research Institute (Radom, Poland) based on an original technology foresight model, which takes into account the results from national and sectoral foresight processes in order to generate and prioritise future research priorities and technologies of the institute. The paper gives evidence of the practical implementation of the institute’s corporate foresight scientific outcomes into the national R&D agenda through the launch of the strategic research programme “Innovative Systems of Technical Support for Sustainable Development of Economy”.